2011
DOI: 10.3109/15563650.2011.602083
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum toxicokinetics in peritoneal dialysis patients

Abstract: This study describes the first population Al TK model in a large group of PD patients, which includes a covariate effect. The model confirms the extensive half-life and tissue distribution of Al in a dialysis-dependent population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although LDH-nanoparticles have been proven to be highly biocompatible in vitro and many approaches have been investigated to modify the LDH surface for reduced potential toxicity, a long-term in vivo toxicity test is still of significance and warranted, considering that some elements (e.g. Al) can possibly lead to side effects if taken above a certain quantity or in the presence of certain physiological environments 3 34 35 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Although LDH-nanoparticles have been proven to be highly biocompatible in vitro and many approaches have been investigated to modify the LDH surface for reduced potential toxicity, a long-term in vivo toxicity test is still of significance and warranted, considering that some elements (e.g. Al) can possibly lead to side effects if taken above a certain quantity or in the presence of certain physiological environments 3 34 35 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another major contributor to accumulation of Al was uremic compounds in patients undergoing chronic dialysis [43]. Kinetic analysis from peritoneal patients has shown that the half-life of Al elimination is probably approximately seven years [44]. The chelating agent deferoxamine can be used to remove excess Al, whereas some deleterious effects were noted [45].…”
Section: Discussionmentioning
confidence: 99%
“…This was traced to a high Al content in dialysate solutions (1.3 μmol/L, current maximum recommended < 0.742 μmol/L). Yue et al (2011) examined 83 of those patients exposed to Al-contaminated dialysate and found the mean serum Al was 1.77 ± 0.74 μmol/L (47 μg/L) compared to a normal upper limit of 6 μg/L (reviewed in Krewski et al 2007). …”
Section: Organ Systems and Functionmentioning
confidence: 99%